1998
DOI: 10.1007/pl00005290
|View full text |Cite
|
Sign up to set email alerts
|

High affinity regulation of cardiac Cl– and Ca2+ conductances by (13R)-spiroforskolin

Abstract: The effects of a new forskolin derivative, (13R)-spiroforskolin, on the ventricular cAMP-activated chloride current (I(Cl(cAMP))) and the atrial L-type calcium current (I(Ca,L)) were measured by means of whole-cell recording from isolated guinea-pig cardiac myocytes at 30 degrees C and 20-22 degrees C, respectively. In contrast to forskolin, the derivative contains a tetrahydrofuran rather than a tetrahydropyran moiety. (13R)-spiroforskolin activated I(Cl(CAMP)) in 58% of the ventricular myocytes studied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
1

Year Published

2000
2000
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
1
1
Order By: Relevance
“…One might argue, therefore, that the effects present or absent during, for example, peptide treatment (Ht31/Ht31P) can be explained by the presence or absence of CFTR expression in the respective cells. However, this interpretation is hardly justified because forskolin (and other cAMP-elevating agents) activated a big I CFTR in almost every cell tested (>90%) in this and two previous studies conducted in our laboratory [25,31]. It does, however, explain the comparatively high standard error of the Cl -current densities seen in the concentration-response curve for forskolin (Fig.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…One might argue, therefore, that the effects present or absent during, for example, peptide treatment (Ht31/Ht31P) can be explained by the presence or absence of CFTR expression in the respective cells. However, this interpretation is hardly justified because forskolin (and other cAMP-elevating agents) activated a big I CFTR in almost every cell tested (>90%) in this and two previous studies conducted in our laboratory [25,31]. It does, however, explain the comparatively high standard error of the Cl -current densities seen in the concentration-response curve for forskolin (Fig.…”
Section: Discussioncontrasting
confidence: 65%
“…Different responses of the forskolin-dependent regulation of I CFTR and I p reveal differences in the PKA-dependent regulation of the two currents Activation of I CFTR in guinea-pig cardiomyocytes by 4 µM forskolin, a maximally effective concentration ( [31], this study), was rapid, starting 15 s after application of the drug and reaching its maximum within less than 60 s. Similar results have been reported by Pelzer and co-workers [30]. At 22°C, they found that 1 µM forskolin activated I CFTR with a time lag of 28 s, the maximum being reached after about 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…1 and ). By contrast, application of 4 μM forskolin, a concentration previously shown to maximally stimulate I Cl(cAMP) in these cells (Traebert et al 1998), activated, after a lag of approximately 20 s, an outward current which was identified as I Cl(cAMP) (see Fig. 8).…”
Section: Resultsmentioning
confidence: 93%
“…Figure 4A shows an original recording of the membrane current of a ventricular myocyte (C m : 209 pF) first challenged with 4 µM forskolin (to stimulate PKA maximally [33,43]) and then, in addition, with 1 µM PDBu (to stimulate PKC maximally). Forskolin caused an outward current shift that was due to the activation of I CFTR (as evidenced by the increase in holding current at zero K + o of +55 pA or +0.26 pA/pF; see below) and a stimulation of I p .…”
Section: Resultsmentioning
confidence: 99%